Microsatellite Instability in Colorectal Cancer: Rethinking the Roles of Age and Family History - Ghanbari Mardasi, Farideh; Eghtedari, Mohsen; Shirkoohi, Reza (Asian Pacific Journal of Cancer Biology, 2026)
Background: Microsatellite instability (MSI) is a hallmark of defective DNA mismatch repair (MMR) and a well-established molecular subtype of colorectal cancer (CRC). MSI testing has gained increasing clinical relevance in the diagnosis of Lynch syndrome (hereditary nonpolyposis colorectal cancer) and in guiding treatment strategies. Objective: This review explores the diagnostic and prognostic implications of MSI in CRC, with a particular emphasis on the role of patient age and family history in identifying high-risk individuals. Methods: We reviewed the current literature on MSI, Lynch syndrome, and familial CRC, including data on molecular mechanisms, screening tools (MSI testing, IHC, predictive models), and epidemiological trends in both hereditary and sporadic CRC cases. Results: MSI-High (MSI-H) status is strongly associated with Lynch syndrome in early-onset CRC cases (<50 years) and in those with positive family history. However, a substantial proportion of MSI-H tumors occur sporadically in older adults (>60 years) without known familial risk, often due to MLH1 promoter hypermethylation. Family history-based screening demonstrates limited sensitivity, missing up to 60% of MSI-H cases. Universal MSI testing improves identification of both hereditary and sporadic cases and is now widely recommended. Moreover, MSI-H tumors show favorable prognosis and are predictive of better response to immunotherapy. Conclusion: While age and family history remain important in assessing CRC risk, they are insufficient as standalone criteria for Lynch syndrome screening. Universal MSI testing offers a more reliable approach for early diagnosis, risk stratification, and treatment planning in colorectal cancer. Further research is needed to refine predictive models and integrate MSI testing into broader population screening protocols.